2017
DOI: 10.1038/ajg.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Ability of High-Resolution Manometry to Determine Feeding Method and to Predict Aspiration Pneumonia in Patients With Dysphagia

Abstract: We first established the optimal thresholds for HRM parameters to determine feeding method and predict the development of aspiration pneumonia in patients with oropharyngeal dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…Park et al reported that aspiration and penetration observed during a videofluoroscopic swallow study and high-resolution manometry were predictors of aspiration pneumonia among patients with dysphagia. 23 Almirall et al reported that oropharyngeal dysphagia is a risk factor for CAP among elderly patients. 24 Moreover, dysphagia related to stroke and Parkinson’s disease is a risk factor of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported that aspiration and penetration observed during a videofluoroscopic swallow study and high-resolution manometry were predictors of aspiration pneumonia among patients with dysphagia. 23 Almirall et al reported that oropharyngeal dysphagia is a risk factor for CAP among elderly patients. 24 Moreover, dysphagia related to stroke and Parkinson’s disease is a risk factor of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal contractile integral reflects oro-pharyngeal functional competency 18 , 34 , 46 . UES and LES Basal tone mmHg.cm.s Continuous Contractile integral (amplitude*length* duration) calculated during a 2 s window at rest prior to basal swallow 36 , 37 UES and LES Relaxation reflex occurrence % Categorical Relaxation defined as > 50% decrease from basal tone 34 , 35 UES Contractile reflex % Categorical Contraction defined as > 50% increase from basal tone- definition adapted from previous works 32 , 33 Esophagus Esophageal contractile vigor mmHg.cm.s Continuous Contractile integral (amplitude*length* duration) of esophageal regions. Proximal esophagus: lower UES border to transition zone.…”
Section: Participants Study Design and Methodsmentioning
confidence: 99%
“…Abnormal HRMF metrics in the UES and proximal esophagus were identified using the following criteria: impaired UES relaxation pressure/duration (relaxation pressure >12 mmHg/<0.45 s), hypertensive resting UES pressure (>104 mmHg), and hypotensive resting UES pressure (<34 mmHg) ( 13 , 14 ). Proximal esophageal contraction integral above 0 mmHg during UES opening (an early response occurring concurrently with UES opening) was also defined as abnormal, a phenomenon observed in this study among MSA patients.…”
Section: Methodsmentioning
confidence: 99%